2010
DOI: 10.3892/or_00001029
|View full text |Cite
|
Sign up to set email alerts
|

An explorative study on the clinical utility of baseline and serial serum tumour marker measurements in advanced upper gastrointestinal cancer

Abstract: Abstract. The value of early tumour marker changes during palliative chemotherapy in patients with upper gastrointestinal adenocarcinoma (UGIA) is unclear. Seventy-three patients with advanced UGIA were randomised to receive 45 mg/m 2 docetaxel or 180 mg/m 2 irinotecan with 5-FU/ leucovorin. After every 2nd course the patients were crossed over to the other regimen. Serum was sampled before start of chemotherapy and every 2nd week during 8 weeks for CEA, TPA, TPS, CA72-4, CA19-9 and CA242 measurements. Eightee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Tumor markers are commonly used in clinical practice, and their baseline levels can provide prognostic information [31]. In gastric cancer, several studies have demonstrated a close association between long-term prognosis and various tumor markers, such as CA72-4, CEA, CA19-9, CA125, and alpha fetoprotein [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers are commonly used in clinical practice, and their baseline levels can provide prognostic information [31]. In gastric cancer, several studies have demonstrated a close association between long-term prognosis and various tumor markers, such as CA72-4, CEA, CA19-9, CA125, and alpha fetoprotein [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%